PENGARUH KETEPATAN WAKTU DAN KUALITAS HASIL MAKE UP TERHADAP KEPUASAN PENGGUNA JASA MAKE UP DI POLRI TV - Angel Prichilia Putri; Nurul Hidayah; Dwi Atmanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of timeliness and makeup quality on customer satisfaction among makeup service users. This research employed a quantitative approach using a survey method. The population consisted of customers who had previously used makeup services, while the sample comprised 30 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire. Prior to data analysis, the research instruments were tested for validity and reliability. The collected data were analyzed using classical assumption tests, including the normality test and multicollinearity test, followed by multiple linear regression analysis, partial test (t-test), simultaneous test (F-test), and coefficient of determination (R²) with the assistance of IBM SPSS Statistics version 23. The findings indicate that, partially, timeliness does not have a significant effect on customer satisfaction, whereas makeup quality has a positive and significant effect on customer satisfaction. Simultaneously, timeliness and makeup quality significantly influence customer satisfaction. The coefficient of determination shows that both independent variables explain a substantial proportion of the variation in customer satisfaction, while the remaining variation is influenced by other factors beyond the scope of this study. Therefore, makeup quality is identified as the most dominant factor in improving customer satisfaction with makeup services.